Analysis on Impact Stress Calculation of Second Combination of the Dual Ratchet Clutch - Shi Hao; Li Zhengminqing; Chen Liqiang (Jixie chuandong)
The response exhibited by a solitary ratchet clutch tends to be languid when subjected to dual aeration, thereby resulting in a substantial impact that bears the potential to inflict damage upon the clutch mechanism. Consequently, a study was conducted on a dual ratchet clutch to achieve dual speed coupling while meeting strength requirements, enhancing the versatility of the ratchet clutch. The structure and principle of a dual ratchet clutch was introduced, a secondary coupling impact model and calculation method were established for impact stress of the dual ratchet clutch, and the accuracy of the model was compared and verified through the simulation analysis. On this basis, the influence of parameters such as the double ratchet structure on it was analyzed. The research results can provide reference for the design of dual ratchet clutches.